Blood pressure and anthropometric measurements in Albanian versus Turkish children and adolescents - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2009)
Objective - Understanding intercultural, regional and interracial differences in blood pressure and anthropometric indices may help to determine the contributors of mortality from coronary artery disease in different populations. Design and setting - In this article we used data collected from two different countries: (a) Survey on school children from Istanbul, Turkey, (b) Cross Sectional Study of Albanian school children. Results - We compared age- and gender-matched Albanian and Turkish children and adolescents (age 11-12 y and 15-17 y) living in 2 different countries with regard to blood pressure, weight, height, body mass index (BMI), waist circumference, hip circumference, waist-to-hip (WHpR) and waist-to-height (WHtR) ratio. We observed significant differences in blood pressure, BMI and other anthropometric indices among age- and gender-matched subjects from the two countries. Birthweight was lower among Turkish children and adolescents compared to Albanian subjects (3258 vs. 35 10 g, P < 0.01). Turkish children had lower BMI and WHtR compared to Albanian children, while adolescents displayed similar BMI and WHtR. Paradoxically, Turkish children and adolescents displayed higher systolic blood pressures compared to Albanian children and adolescents. Significant differences were observed in the dietary intake and physical activity, which may partially explain the differences in blood pressure and anthropometric indices. Conclusions - The socio-economic, dietary and physical activity status may account for significant differences in blood pressure and anthropometric indices of children and adolescents living in two different countries. Future studies should focus on the ethnic differences in the definition and prevention of cardiovascular risks among children and adolescents.
Keywords: Blood pressure; anthropometric indices; Albanian; Turkish; BODY-MASS INDEX; POPULATION-BASED SURVEY; TO-HEIGHT RATIO; PHYSICAL-ACTIVITY; WAIST CIRCUMFERENCE; METABOLIC SYNDROME; RISK-FACTORS; TIRANA CITY; OVERWEIGHT; HYPERTENSION